Personality Traits and Exercise Capacity in Male Athletes and Non-Athletes. Issue 1 (February 2014) - Malinauskas, Romualdas; Dumciene, Audrone; Mamkus, Gediminas; Venckunas, Tomas
To investigate the relationships between personality traits and athletic capacity, this study compared a sample of 376 young adult men (169 athletes, 207 non-athletes; M age = 23.8 yr., SD = 3.9). 26 lab-based exercise capacity parameters were measured, as well as the Big Five major personality traits using the NEO Five-Factor Inventory. The results indicated that athletes scored higher than non-athletes for Conscientiousness but scores were not statistically different between groups for other personality traits. Team sport athletes scored higher on Extraversion than endurance athletes. All the personality traits were associated with some of the exercise capacity indices; however, these correlations were rather weak ( rs < .2).